2022
DOI: 10.1016/j.bioactmat.2021.05.051
|View full text |Cite
|
Sign up to set email alerts
|

Ionizable lipid-assisted efficient hepatic delivery of gene editing elements for oncotherapy

Abstract: CRISPR/Cas9-based gene editing has emerged as a powerful biotechnological tool, that relies on Cas9 protein and single guided RNA (sgRNA) to edit target DNA. However, the lack of safe and efficient delivery carrier is one of the crucial factors restricting its clinical transformation. Here, we report an ionizable lipid nanoparticle (iLP181, p K a = 6.43) based on iLY1809 lipid enabling robust gene editing in vitro and in vivo . The iLP181 eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 49 publications
0
37
0
Order By: Relevance
“…Huang et al reported an ionizable LNP iLP181 of iLY1809 (p K a = 6.43) to deliver psgPLK1 plasmid for treating liver cancer. [ 173 ] iLP181 showed neutral zeta potential at pH 7.4 and can be protonated in the endosome of acid environment. Protonated lipids can destroy the stability of the endosomal membrane and promote the escape of nucleic acid molecules from the endosome to the cytoplasm.…”
Section: Delivery Of Plasmid Expressing Cas9 Nuclease and Sgrnamentioning
confidence: 99%
“…Huang et al reported an ionizable LNP iLP181 of iLY1809 (p K a = 6.43) to deliver psgPLK1 plasmid for treating liver cancer. [ 173 ] iLP181 showed neutral zeta potential at pH 7.4 and can be protonated in the endosome of acid environment. Protonated lipids can destroy the stability of the endosomal membrane and promote the escape of nucleic acid molecules from the endosome to the cytoplasm.…”
Section: Delivery Of Plasmid Expressing Cas9 Nuclease and Sgrnamentioning
confidence: 99%
“…Cationic or ionizable lipids are the primary substance to deliver RNA such as (i) 1,2-dioleoyl-sn-glycerol-3-phosphoethanolamine (DOPE) [ 111 ], (ii) N-[1-(2,3-dioleoyloxy) propyl]- N , N , N -trimethylammonium chloride (DOTMA) [ 112 ], (iii) N1,N3,N5-tris(3-(didodecylamino)-propyl)benzene-1,3,5-tricarboxamide (TT3) [ 113 ], (iv) dilinoleylmethyl-4-dimethylaminobutyrate (Dlin-MC3-DMA), (v) N , N -Dimethyl-2,3-bis[(9Z,12Z)-octadeca-9,12-dienyloxy]propan-1-amine (DLinDMA) [ 114 ] and (vi) 1,2-dioleoyloxy-3-trimethylammonium propane chloride (DOTAP) [ 115 ]. At certain pH, these lipids are positively charged and thus feasible for the mRNA to interact electrostatically, and easily fused with cellular membrane [ 116 ]. After endocytosis, the ionizable cationic lipid becomes more positively charged due to proton-pump mediated pH reduction [ 117 ].…”
Section: Mrna Delivery Technologiesmentioning
confidence: 99%
“…The PLK1 gene has also been targeted in related studies of liver cancer. Li et al constructed a proprietary ionizable lipid nanoparticle named iLP181 ( Li et al, 2022 ). Four plasmids containing PLK1-targeting Cas9 protein and sgRNA were designed.…”
Section: Applications and Effects Of Gene Editing Based On Nano-drug ...mentioning
confidence: 99%